Risk factors for Blastocystis infection in HIV/AIDS patients with highly active antiretroviral therapy in Southwest China - Shun-Xian Zhang; Fen-Yan Kang; Jia-Xu Chen; Li-Guang Tian; Lan-Lan Geng (BMC, 2019)
Abstract Background Blastocystis is a widespread zoonotic protozoan of mammalian species, especially in HIV/AIDS individuals. The aim of this study was to analyze the prevalence and risk factors related with Blastocystis infection among HIV/AIDS patients in Southwest China. Methods The cross-sectional study was performed in 311 HIV/AIDS cases in Tengchong City, Yunnan Province from July 2016 to March 2017. For each subject, stool specimen was collected to detect the Blastocystis, and the blood sample was used to detect HIV virus load and CD4+ T cell count, in addition, structured questionnaire was used to collect the basic information and risk factors. Findings The result showed that the detection rate of Blastocystis was 3.86% (95% CI: 2.22-6.62) among HIV/AIDS patients. Both raising animal (OR = 12.93, 95% CI: 1.54-108.36) and drinking un-boiled water (OR = 8.17, 95% CI: 1.76-37.90) were risk factors for Blastocystis infection in HIV/AIDS individuals. In addition, the interaction of CD4+ T cell count and HIV virus load was also contribution to Blastocystis infection (P = 0.007). Conclusions A high prevalence of Blastocystis infection was found in HIV/AIDS patients in Tengchong. Poor hygienic habits, the interaction of HIV virus load and CD4+ T cell count were identified as main risk factors for infection. These results will help us to develop efficient control strategies to intervene with and prevent the occurrence of Blastocystis among HIV-infected individuals.